PERANAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENURUNAN KONTRIBUSI PAJAK HOTEL PADA PENDAPATAN ASLI DAERAH KOTA SURABAYA TAHUN 2009-2013 - NAHDYA PUTRI, LINTANG (Jurnal Akuntansi AKUNESA, 2015)
ABSTRAK This research used to analyze some factors that affect degression of contribution hotel tax at regional revenue in Surabaya City during 2009-2013. This research uses qualitatif method within case setudy. From the analysis, obtained there are two main factors, are lack of effectiveness to collect hotel tax by fiscus and increase other local tax resources. Therefore, the conclusion is the growth factors of regional revenue bigger than growth of hotel tax. Keywords : Hotel Tax, contribution, regional revenue, factors